Larangan Riba dalam Jual Beli: Tinjauan Normatif dan Teologis dalam Perspektif Islam - Rudi Hartono I; Hanifa Missirman K; Ilma Wahyu Bilhiyati; Arfatul Marwah Tanjung (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Usury in buying and selling is a practice that is forbidden in Islam because it contradicts the principles of justice and balance in economic transactions. This research uses a qualitative approach with a literature study method to explore the normative and theological understanding of usury based on the Qur'an, hadith, and the views of scholars. Islam forbids all forms of usury, both in debt and buying and selling, including usury of qardh, jahiliyyah, fadhl, yad, and nasi'ah. This prohibition aims to prevent exploitation and create a fair economic system. Although some scholars still debate the status of bank interest, the majority state that the practice is usury. This study emphasizes the importance of staying away from usury and encourages the use of sharia-compliant transaction systems such as murabahah and mudharabah.